2005
DOI: 10.1536/ihj.46.97
|View full text |Cite
|
Sign up to set email alerts
|

Primary Congenital Anomalies of the Coronary Arteries: A Coronary Arteriographic Study in Western Turkey

Abstract: SUMMARYCoronary artery anomalies are found in 0.6% to 1.5% of coronary angiograms. Angiographic recognition of these vessels is important because of their clinical significance and importance in patients undergoing coronary angioplasty or cardiac surgery.We reviewed the database of the Cardiac Catheterization Laboratory of Uludag Medical University in Bursa, Turkey. All patients who were subjected to coronary angiography from 1994 to 2001 were included.The study included 12,059 patients who underwent diagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
19
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 24 publications
4
19
3
Order By: Relevance
“…Worldwide incidence has been described previously. We found an overall incidence of congenital anomalous aortic origin of the coronary artery of 1.3% among patients undergoing coronary artery angiography; this is in agreement with the 0.16-1.3% incidence reported in other series 7-9)12-15). Anomalous coronaries prevailed among males, possibly due to the fact that more angiograms were done among male patients.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Worldwide incidence has been described previously. We found an overall incidence of congenital anomalous aortic origin of the coronary artery of 1.3% among patients undergoing coronary artery angiography; this is in agreement with the 0.16-1.3% incidence reported in other series 7-9)12-15). Anomalous coronaries prevailed among males, possibly due to the fact that more angiograms were done among male patients.…”
Section: Discussionsupporting
confidence: 92%
“…Although the literature suggests that the majority of coronary artery fistulae open into the RV, right atrium, and CS, and less common into the PA, LA, or LV,7) we obtained the opposite results. We encountered 4 patients with significant coronary-to-cameral fistulae.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Unfortunately, most of the previous studies focussed on AOCs. 9 16 These studies did not use the same classification system to define CAA. Some groups included solely AOCs in their study population, while others included AOCs together with coronary termination anomalies (i.e., using a modified classification).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that LCX anomalies were the third most common coronary artery anomaly diagnosed by using CAG 3). A total of 71% of patients with LCX anomaly had significant stenosis of the proximal LCX and 11% had severe atherosclerosis in this vessel alone 4).…”
Section: Discussionmentioning
confidence: 99%